Separation composite membrane as well as preparation method and application thereof

By designing a separation composite membrane composed of a support layer, a silicone rubber intermediate layer and a crosslinked polymer layer, the problem of difficulty in achieving high permeability and selectivity in the prior art is solved, high CO2 flux and separation coefficient are achieved, and the preparation process is simplified.

CN119549002AActive Publication Date: 2025-03-04CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311127284.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2025-03-04
Estimated Expiration
2043-09-01

AI Technical Summary

Technical Problem

The prior art is difficult to achieve high permeability and selectivity at the same time, and the preparation process of thin-layer composite films takes a long time.

Method used

A separation composite film is designed, consisting of a sequentially stacked support layer, a silicone rubber intermediate layer and a crosslinked polymer layer. The crosslinked polymer comprises structural units from polyamine compounds, polyacid chloride compounds and polyphenol compounds, and is prepared by interfacial polymerization.

Benefits of technology

High CO2 flux and high separation coefficients between CO2 and N2 are achieved, which simplifies the preparation process and improves the film formation efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549002A_ABST
    Figure CN119549002A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of membrane separation materials, and discloses a separation composite membrane and a preparation method and application thereof.The separation composite membrane comprises a supporting layer, a silicone rubber middle layer and a polymer layer which are sequentially stacked; a polymer forming the polymer layer comprises a structural unit I from a polyamine compound, a structural unit II from a polyacyl chloride compound and a structural unit III from a polyphenol compound. The separation composite membrane has a relatively high CO2 flux and a relatively high CO2 and N2 separation coefficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of membrane separation materials, and in particular to a separation composite membrane and a preparation method thereof, and application of the separation composite membrane in CO2 separation. Background Art

[0002] Since the Industrial Revolution, the burning of large amounts of fossil fuels has led to an increase of nearly 50% in the concentration of CO2 in the atmosphere, and it is expected to continue to rise. The emission of greenhouse gases such as CO2 is the main cause of global warming. As energy and environmental issues become increasingly severe, reducing greenhouse gas emissions and improving carbon utilization efficiency have become hot topics of concern to the international community today. Therefore, separating and recovering CO2 from emission sources and using certain methods to achieve the conversion and utilization of CO2 have become the focus of scientific and technological research at home and abroad. CO2 separation membrane technology has aroused widespread research interest due to its advantages such as simple equipment, low fixed investment and low energy consumption.

[0003] Membrane separation technology uses the difference in the permeation rate of various gases in different membrane materials to achieve separation, and the permeability of gases through membranes is related to the properties of gas molecules, the properties of the membrane, and the interaction between the gas and the membrane. CO2 separation membranes often promote the permeation of CO2 in the membrane by introducing groups that interact with CO2 (such as amine groups, ether groups, etc.) into the membrane, so that CO2 is enriched on the permeation side of the membrane after passing through the membrane, while gases with relatively slow permeation rates (such as N2, CH4) are enriched on the retention side of the membrane, thereby separating the mixed gas.

[0004] At present, CO2 separation membranes prepared from a single polymer are generally difficult to have both high selectivity and permeability. Compared with homogeneous membranes, thin-layer composite membrane structures have a porous layer to provide mechanical support, which can greatly reduce the thickness of the effective selective layer above, thereby reducing the overall mass transfer resistance and achieving higher flux. Therefore, most of the high-performance polymer membranes currently used for CO2 separation are thin-layer composite membranes. Thin-layer composite membranes are usually prepared using interfacial polymerization. However, the polyamide structure composite membranes obtained by the prior art often have the problems of being relatively dense, relatively thick, and difficult to control the overall microstructure and surface morphology.

[0005] US5650479A discloses a composite membrane with a separation layer having a cross-linked polyarylate structure, and a multifunctional phenol is used as a water phase monomer in the preparation process. However, since the internal cavity of the polyester cross-linked structure is generally large, although the membrane has good permeability, the achievable gas selectivity is limited.

[0006] In summary, it is difficult for thin-layer composite membrane structures prepared by existing technologies to achieve high permeability and selectivity at the same time, and the preparation process of some membranes is time-consuming. Therefore, it is necessary to design a CO2 separation membrane that has both high permeability and selectivity and high preparation efficiency. Summary of the invention

[0007] The purpose of the present invention is to overcome the problem that the separation membrane in the prior art cannot have both high flux and high selectivity, and to provide a separation composite membrane and its preparation method and application, wherein the separation composite membrane has a higher CO2 flux and a higher separation coefficient between CO2 and N2.

[0008] In order to achieve the above-mentioned object, the first aspect of the present invention provides a separation composite membrane, wherein the separation composite membrane comprises a support layer, a silicone rubber intermediate layer and a polymer layer stacked in sequence;

[0009] The cross-linked polymer constituting the polymer layer includes a structural unit I derived from a polyamine compound, a structural unit II derived from a polyacyl chloride compound, and a structural unit III derived from a polyphenol compound.

[0010] A second aspect of the present invention provides a method for preparing a separation composite membrane, wherein the method comprises:

[0011] (1) preparing a casting solution and heating it, preparing a support layer by a non-solvent phase conversion method, and then washing it with water;

[0012] (2) applying the silicone rubber solution on the support layer by scraping, and performing coating and curing treatment to prepare a silicone rubber intermediate layer on the support layer;

[0013] (3) preparing a polymer layer on the silicone rubber intermediate layer by interfacial polymerization of oil phase monomers in the oil phase solution and water phase monomers in the water phase solution to obtain the separation composite membrane;

[0014] Wherein, the oil phase monomer is selected from polyacyl chloride compounds;

[0015] The aqueous phase monomer is selected from polyamine compounds and polyphenol compounds.

[0016] The third aspect of the present invention provides a separation composite membrane prepared by the aforementioned preparation method.

[0017] A fourth aspect of the present invention provides an application of the aforementioned separation composite membrane in CO2 separation.

[0018] Through the above technical solution, the present invention has the following beneficial effects:

[0019] (1) The separation composite membrane prepared by the present invention is thin, and the support layer, rubber intermediate layer and polymer layer stacked in sequence are closely attached to each other, thereby improving the flux of the separation composite membrane to CO2;

[0020] (2) The polyphenol compound has a non-planar structure, which makes the cross-linked polymer in the obtained polymer layer have more free volume; at the same time, there are unreacted amino groups from the polyamine compound in the polymer, which promote the transfer of CO2; the two cooperate with each other to improve the flux of CO2 through the separation composite membrane; at the same time, the separation composite membrane can selectively pass gases of different sizes, and can effectively separate CO2 and N2;

[0021] (3) In the interfacial polymerization reaction process, the polyamine compound reacts with the polyacyl chloride compound, and the polyphenol compound reacts with the polyacyl chloride compound. The polyamine compound reacts with the polyacyl chloride compound at a faster rate, thereby solving the problem of low reaction activity and long reaction time when only a single polyphenol compound and a polyacyl chloride compound undergo interfacial polymerization reaction, thereby improving the membrane preparation efficiency. At the same time, it solves the problem of high thickness of the separation composite membrane, which is not conducive to gas passage, when only a single polyamine compound and a polyacyl chloride compound undergo interfacial polymerization reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is the total reflection infrared absorption spectrum of the surface layer of the separation composite membrane C2 prepared in Example 2 of the present invention;

[0023] Figure 2 This is an electron microscope image of the cross section of the separation composite membrane C7 prepared in Example 7 of the present invention. DETAILED DESCRIPTION

[0024] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0025] A first aspect of the present invention provides a separation composite membrane, wherein the separation composite membrane comprises a support layer, a silicone rubber intermediate layer and a polymer layer stacked in sequence;

[0026] The cross-linked polymer constituting the polymer layer includes a structural unit I derived from a polyamine compound, a structural unit II derived from a polyacyl chloride compound, and a structural unit III derived from a polyphenol compound.

[0027] In the present invention, the structure of the cross-linked polymer can be measured and analyzed by infrared spectroscopy and XPS spectrum.

[0028] In the present invention, the specific cross-linked polymer structure improves the stability of the separation composite membrane. At the same time, the structural unit III derived from the polyphenol compound has a non-planar structure, which gives the polymer layer more free volume. The structural unit I derived from the polyamine compound has unreacted amino groups, which promotes the transfer of CO2. The two work synergistically with each other to improve the CO2 flux of the separation composite membrane and enable the separation composite membrane to have a higher CO2 and N2 separation coefficient.

[0029] According to the present invention, the cross-linked polymer further comprises the general formula The connecting group a connecting the structural unit I and the structural unit II shown in the general formula The connecting group b shown connects the structural unit II and the structural unit III.

[0030] There are several possible ways of cross-linking in cross-linked polymers:

[0031] When the self-functionality of the polyacyl chloride compound is ≥3, the polyacyl chloride compound can form structural unit II, and the unreacted acyl chloride functional groups in the structure form connecting groups a or b with the unreacted amino groups of the polyamine compounds and the unreacted hydroxyl groups of the polyphenol compounds on different macromolecular chains, thereby forming a cross-linked structure; the polyacyl chloride compound may also not participate in the construction of the chain segments, but only exist between different macromolecular chains, and the acyl chloride functional groups in the structure of the polyacyl chloride compound form connecting groups a or b with the unreacted amino groups of the polyamine compounds and the unreacted hydroxyl groups of the polyphenol compounds on different macromolecular chains.

[0032] When the self-functionality of the polyacyl chloride compound is 2, when the polyacyl chloride compound acts as a cross-linking agent, it only exists between different macromolecular chains. The acyl chloride functional groups in the structure of the polyacyl chloride compound form connecting groups a or b with the unreacted amino groups of the polyamine compounds and the unreacted hydroxyl groups of the polyphenol compounds on different macromolecular chains; the polyacyl chloride compounds participating in the construction of the chain segments no longer act as cross-linking agents.

[0033] According to the present invention, the molar ratio of the linking group a to the linking group b is 0.1-10:1.

[0034] In the present invention, the molar ratio of the connecting group a to the connecting group b can be calculated by the peak areas of the amide group and the ester group in the XPS spectrum. When the connecting group a and the connecting group b meet the above range, the separation composite membrane has a higher CO2 flux and CO2 and N2 separation coefficient.

[0035] More preferably, the molar ratio of the linking group a to the linking group b is 0.5-5:1.

[0036] According to the present invention, the polyamine compound is selected from at least one of m-phenylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, 1,4-cyclohexanediamine, 1,3-diamino-2-methylpropane, bis(2-aminoethyl) ether, ethylene glycol bis(2-aminoethyl) ether, diethylene glycol di(3-aminopropyl) ether, 1,4-butanediol bis(3-aminopropyl) ether and 1,4-bis(3-aminopropyl) piperazine, preferably selected from at least one of triethylenetetramine, tetraethylenepentamine, diethylene glycol di(3-aminopropyl) ether and 1,4-bis(3-aminopropyl) piperazine.

[0037] According to the present invention, the polybasic acid chloride compound is selected from at least one of trimesoyl chloride, isophthaloyl chloride and 3,3,4,4-biphenyltetracarboxylic acid chloride, preferably trimesoyl chloride.

[0038] According to the present invention, the polyphenol compound is selected from at least one of phloroglucinol, 1,2,4,5-pyrogallol, 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane, 9,9-bis(4-hydroxyphenyl)fluorene and 2,2',3,3'-tetrahydroxy-1,1'-binaphthyl, preferably selected from 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane and / or 9,9-bis(4-hydroxyphenyl)fluorene.

[0039] In the present invention, the polymer prepared from the polyamine compounds, polyacyl chloride compounds and polyphenol compounds meeting the above types is more stable, so that the separation composite membrane has both a higher CO2 flux and a CO2 and N2 separation coefficient.

[0040] According to the present invention, the silicone rubber intermediate layer includes silicone rubber.

[0041] According to the present invention, the viscosity of the silicone rubber at 25° C. is 0.1-50000 cP.

[0042] In the present invention, the silicone rubber meeting the above viscosity range has good fluidity, and can make the prepared silicone rubber middle layer uniform and flat, which is beneficial to improving the flux of CO2.

[0043] Viscosity can be measured using a spindle viscometer.

[0044] Furthermore, the viscosity of the silicone rubber at 25° C. is 50-4000 cP.

[0045] According to the present invention, the material constituting the support layer is polysulfone and / or polyethersulfone.

[0046] According to the present invention, the weight average molecular weight of the material of the support layer is 2000-400000 Da, preferably 3000-6000 Da.

[0047] The weight average molecular weight of the material of the support layer can be determined by the GPC method.

[0048] According to the present invention, the support layer has a porous structure.

[0049] According to the present invention, the porosity of the support layer is 10-80%.

[0050] According to the present invention, the average pore size of the support layer is 1-5000 nm.

[0051] In the present invention, the porosity of the support layer is tested by dividing the pore area in the field of view by the total surface area through a scanning electron microscope; the average pore size of the support layer is tested by measuring the diameters of all visible pores in the field of view through a scanning electron microscope and calculating the average value.

[0052] In the present invention, the support layer that meets the above-mentioned specific range of porosity and average pore size can allow gas to pass through, and the surface of the generated support layer is relatively smooth, which is conducive to preparing a silicone rubber intermediate layer on its surface, making the layers more fitted, thereby improving the stability of the separation composite membrane.

[0053] Furthermore, the porosity of the support layer is 40-70%.

[0054] Furthermore, the average pore size of the support layer is 5-200 nm.

[0055] According to the present invention, the average thickness of the support layer is 20-500 μm, the average thickness of the silicone rubber intermediate layer is 50-900 nm, and the average thickness of the polymer layer is 10-500 nm.

[0056] In the present invention, the thickness of the layer membrane meets the above range, so that the mass transfer resistance of the separation composite membrane as a whole is small, and the flux of the separation composite membrane to CO2 is improved.

[0057] Furthermore, the average thickness of the support layer is 60-150 μm, the average thickness of the silicone rubber intermediate layer is 50-500 nm, and the average thickness of the polymer layer is 50-250 nm.

[0058] According to the present invention, the cross-linking degree of the cross-linked polymer is 40-70%, preferably 50-65%.

[0059] It can be calculated by XPS and infrared spectroscopy.

[0060] According to the present invention, the polymer layer has a microporous structure.

[0061] According to the present invention, the average pore size of the polymer layer is 0.1-1 nm.

[0062] In the present invention, the average pore size of the polymer layer is tested according to the standard GB / T 42269-2022 "Test method for pore size of separation membranes - gas permeation method".

[0063] In the present invention, the average pore size of the polymer layer that meets the above range can screen gas molecules of different sizes, allowing only small gas molecules to pass through, thereby achieving gas selective separation, and can be used to separate CO2 and N2.

[0064] Furthermore, the average pore size of the polymer layer is 0.3-0.6 nm.

[0065] According to the present invention, the material of the support layer is not particularly limited and may be a material commonly used in the art that can play a certain supporting role. Preferably, the support layer is polysulfone and / or polyethersulfone.

[0066] According to the present invention, the CO2 flux of the separation composite membrane is ≥200 GPU, preferably ≥350 GPU.

[0067] According to the present invention, the separation coefficient of CO2 and N2 of the separation composite membrane is ≥30, preferably ≥50.

[0068] In the present invention, the flux of CO2 and the flux of N2 can be determined respectively by the pressure difference method, and the specific method is carried out in accordance with GB / T1038.1-2022 "Test method for gas permeability of plastic film and sheet - Part 1: Differential pressure method"; the separation coefficient calculation formula of CO2 and N2 is: separation coefficient of CO2 and N2 = flux of CO2 / flux of N2.

[0069] The thickness of each layer in the separation composite membrane can be determined by the following detection method: the thickness of the support layer is measured by using a spiral micrometer to measure the dry support layer, and the average value is calculated by measuring 5 points, accurate to 1μm; the thickness of the silicone rubber middle layer is the average value of the transition part between the upper edge area of ​​the support layer and the lower edge area of ​​the top layer in the SEM image, accurate to 1nm; the thickness of the functional layer is the distance from the top surface of the entire membrane to the boundary of the support layer in the SEM image minus the thickness of the middle layer, accurate to 1nm.

[0070] A second aspect of the present invention provides a method for preparing a separation composite membrane, wherein the method comprises:

[0071] (1) preparing a casting solution and heating it, preparing a support layer by a non-solvent phase conversion method, and then washing it with water;

[0072] (2) applying the silicone rubber solution on the support layer by scraping, and performing coating and curing treatment to form a silicone rubber intermediate layer on the support layer;

[0073] (3) preparing a polymer layer on the silicone rubber intermediate layer by interfacial polymerization of oil phase monomers in the oil phase solution and water phase monomers in the water phase solution to obtain the separation composite membrane;

[0074] Wherein, the oil phase monomer is selected from polyacyl chloride compounds;

[0075] The aqueous phase monomer is selected from polyamine compounds and polyphenol compounds.

[0076] In the present invention, the inventors unexpectedly discovered that in the interfacial polymerization reaction, a specific polyamine compound reacts with a polyacyl chloride compound, and a specific polyphenol compound also reacts with a polyacyl chloride compound. When the polyphenol compound and the polyamine compound are added at the same time, the polyamine compound plays a role similar to a catalyst for the interfacial polymerization reaction of the polyphenol compound and the polyacyl chloride compound. The synergistic effect of the two solves the problems of low activity and long reaction time in the interfacial polymerization reaction of a single polyphenol compound and a polyacyl chloride compound, improves the reaction speed of the interfacial polymerization reaction, and solves the problem that when only a single polyamine compound and a polyacyl chloride compound are present for the interfacial polymerization reaction, the thickness of the obtained separation composite membrane is high, which is not conducive to the passage of gas.

[0077] In the present invention, the separation composite membrane prepared according to the above steps has a higher CO2 flux and a CO2 and N2 separation coefficient, and the preparation method is simple and is conducive to industrial promotion.

[0078] According to the present invention, the casting solution comprises dimethylacetamide, polysulfone and a casting additive.

[0079] According to the present invention, the film casting additive is selected from polyvinyl pyrrolidone and / or polyethylene glycol.

[0080] According to the present invention, based on the total weight of the casting solution, the content of dimethylacetamide is 60wt%-80wt%, the content of polysulfone is 16wt%-24wt%, and the content of the casting additive is 10wt%-15wt%.

[0081] In the present invention, the support layer prepared by meeting the above concentration range has a suitable pore size and porosity, which is conducive to scraping the silicone rubber solution on the surface thereof.

[0082] Furthermore, based on the total weight of the casting solution, the content of dimethylacetamide is 65wt%-75wt%, the content of polysulfone is 18wt%-22wt%, and the content of the casting additive is 12wt%-14wt%.

[0083] According to the present invention, the heating temperature is 50-90° C., preferably 65-80° C.; the heating time is 12-72 hours, preferably 24-70 hours.

[0084] According to the present invention, the water washing is a common method in the art, and can clean the residual solvent and additives. Preferably, the water washing time is ≥12h; preferably ≥36h.

[0085] According to the present invention, the silicone rubber solution is a polysiloxane solution, preferably a polydimethylsiloxane solution.

[0086] According to the present invention, the concentration of the silicone rubber solution is 0.5wt%-5wt%.

[0087] In the art, the concentration of the silicone rubber solution that meets the above range can make the thickness of the prepared silicone rubber intermediate layer thinner, thereby improving the flux of the separation composite membrane for CO2.

[0088] Furthermore, the concentration of the silicone rubber solution is 1wt%-2.5wt%.

[0089] According to the present invention, the scraping method is to use a scraper for scraping, and the thickness of the scraper is 50-500 μm.

[0090] In the present invention, the scraper thickness that meets the above range can make the scraping more complete, so that the prepared silicone rubber intermediate layer is smoother, which is helpful for preparing the polymer layer thereon.

[0091] Furthermore, the scraper has a thickness of 100-150 μm.

[0092] According to the present invention, the coating and curing temperature is 25-70° C.; the coating and curing time is 0.5-48 hours.

[0093] In the present invention, satisfying the preparation conditions within the above range can make the reaction more complete and the prepared silicone rubber intermediate layer have better chemical stability.

[0094] Furthermore, the coating curing temperature is 30-55° C.; the coating curing time is 8-16 hours.

[0095] According to the present invention, the weight ratio of the water phase monomer to the oil phase monomer is 1:1-5.

[0096] In the present invention, the weight ratio satisfying the above range can make the interfacial polymerization reaction proceed more fully, and the separation composite membrane finally prepared can take into account both high gas flux and high gas selectivity.

[0097] Furthermore, the weight ratio of the water phase monomer to the oil phase monomer is 1:2-4.

[0098] According to the present invention, in the aqueous phase solution, the concentration of the aqueous phase monomer is 0.05wt%-2wt%.

[0099] According to the present invention, in the oil phase solution, the concentration of the oil phase monomer is 0.05wt%-2wt%.

[0100] In the present invention, the concentrations of the water phase monomers and the oil phase monomers that meet the above range can make the interfacial polymerization more complete, the prepared polymer layer thinner, and the free volume of the polymer constituting the polymer layer larger, so that the prepared separation composite membrane has both a higher CO2 flux and a CO2 and N2 separation coefficient.

[0101] Furthermore, in the aqueous phase solution, the concentration of the aqueous phase monomer is 0.1 wt%-0.3 wt%.

[0102] Furthermore, in the oil phase solution, the concentration of the oil phase monomer is 0.2wt%-0.6wt%.

[0103] According to the present invention, in the aqueous solution, the concentration of the polyphenol compound is 0.02wt%-0.15wt%.

[0104] According to the present invention, in the aqueous phase solution, the concentration of the polyamine compound is 0.05wt%-0.2wt%.

[0105] In the present invention, when the concentration of the aqueous phase monomer meets the above range, the reaction can proceed quickly and fully, thereby improving the film-making efficiency and meeting the production needs.

[0106] Furthermore, in the aqueous phase solution, the concentration of the polyphenol compound is 0.04wt%-0.1wt%.

[0107] Furthermore, in the aqueous phase solution, the concentration of the polyamine compound is 0.1wt%-0.18wt%.

[0108] According to the present invention, the weight ratio of the polyamine compound to the polyphenol compound is 0.1-9:1.

[0109] In the present invention, when the weight ratio of the polyamine compound to the polyphenol compound satisfies the above range, the reaction rate of the interfacial polymerization reaction can be increased, and the separation composite membrane finally prepared has both high flux and high selectivity.

[0110] Furthermore, the weight ratio of the polyamine compound to the polyphenol compound is 0.2-4:1.

[0111] According to the present invention, the aqueous phase monomer is selected from polyphenol compounds and polyamine compounds.

[0112] According to the present invention, the polyphenol compound is selected from at least one of phloroglucinol, 1,2,4,5-pyrogallol, 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane, 9,9-bis(4-hydroxyphenyl)fluorene and 2,2',3,3'-tetrahydroxy-1,1'-binaphthyl, preferably selected from 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane and / or 9,9-bis(4-hydroxyphenyl)fluorene.

[0113] According to the present invention, the polyamine compound is selected from at least one of m-phenylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, 1,4-cyclohexanediamine, 1,3-diamino-2-methylpropane, bis(2-aminoethyl) ether, ethylene glycol bis(2-aminoethyl) ether, diethylene glycol di(3-aminopropyl) ether, 1,4-butanediol bis(3-aminopropyl) ether and 1,4-bis(3-aminopropyl) piperazine, preferably selected from at least one of triethylenetetramine, tetraethylenepentamine, diethylene glycol di(3-aminopropyl) ether and 1,4-bis(3-aminopropyl) piperazine.

[0114] According to the present invention, the polybasic acid chloride compound is selected from at least one of trimesoyl chloride, isophthaloyl chloride and 3,3,4,4-biphenyltetracarboxylic acid chloride, preferably trimesoyl chloride.

[0115] According to the present invention, the oil phase solution further comprises an oil phase solvent, and the oil phase solvent is selected from at least one of n-hexane, n-heptane and isoparaffin.

[0116] According to the present invention, the isoparaffin is selected from Iospar G and / or Isopar E. Both are solvent oil products of ExxonMobil.

[0117] According to the present invention, the interfacial polymerization reaction further comprises: adding an additive to the aqueous solution to adjust the pH of the interfacial polymerization reaction to 9-13.

[0118] In the present invention, the adjustment of pH refers to the adjustment of the entire aqueous solution system.

[0119] In the present invention, when the reaction conditions are within the above pH range, the interfacial polymerization reaction can proceed more smoothly.

[0120] Furthermore, in the interfacial polymerization reaction, an additive is added to the aqueous solution to adjust the pH to 10-12.

[0121] According to the present invention, the additive is selected from sodium hydroxide and / or sodium carbonate.

[0122] In the present invention, the additive can not only adjust the pH, but also part of the sodium hydroxide reacts with the phenolic hydroxyl group to generate sodium salt, which can enhance the nucleophilicity of the polyphenol compound and make the interfacial polymerization reaction easier to proceed.

[0123] The interfacial polymerization reaction in the present invention is a conventional interfacial polymerization reaction method in the art, wherein, in a particularly preferred method, the process of the interfacial polymerization reaction includes first contacting the upper surface of the material of the silicone rubber intermediate layer with the oil phase solution, and then contacting the upper surface with the water phase solution for a second time.

[0124] In the present invention, the contacting method is a common contacting method in the art, preferably immersion.

[0125] According to the present invention, the first contacting time is 2-10 min, preferably 3-5 min.

[0126] According to the present invention, the reaction temperature of the interfacial polymerization reaction is 15-50° C.; the reaction time of the interfacial polymerization reaction is 0.5-60 min.

[0127] In the present invention, the reaction conditions of the interfacial polymerization reaction that meet the above range can make the prepared polymer have a specific structural unit content, so that the prepared separation composite membrane can have both a higher CO2 flux and a CO2 and N2 separation coefficient.

[0128] Furthermore, the reaction temperature of the interfacial polymerization reaction is 20-30° C.; the reaction time of the interfacial polymerization reaction is 1-5 min.

[0129] In the present invention, in the interfacial polymerization reaction, a specific polyamine compound reacts with a polyacyl chloride compound, and a specific polyphenol compound also reacts with a polyacyl chloride compound. When the polyphenol compound and the polyamine compound are added at the same time, the polyamine compound plays a role similar to that of a catalyst during the reaction between the polyacyl chloride and the polyphenol compound. The synergistic effect of the two solves the problem of low activity and long reaction time when only the interfacial polymerization reaction between the polyacyl chloride compound and the polyphenol compound exists, thereby improving the reaction speed of the interfacial polymerization reaction.

[0130] In the present invention, the ratio of the silicone rubber solution to the membrane area of ​​the support layer is 0.01-0.0375 mL / cm 2 .

[0131] In the present invention, the ratio of the oil phase solution to the membrane area of ​​the silicone rubber intermediate layer of the separation composite membrane is 0.05-0.125 mL / cm 2 .

[0132] In the present invention, the ratio of the aqueous phase solution to the membrane area of ​​the silicone rubber intermediate layer of the separation composite membrane is 0.05-0.125 mL / cm 2 .

[0133] The third aspect of the present invention provides a separation composite membrane produced by the above-mentioned preparation method.

[0134] A fourth aspect of the present invention provides an application of the aforementioned separation composite membrane in CO2 separation.

[0135] The present invention will be described in detail below through examples.

[0136] In the following examples and comparative examples,

[0137] The weight average molecular weight of the material of the support layer can be determined by the GPC method;

[0138] The porosity of the support layer is measured by scanning electron microscopy and obtained by dividing the pore area within the field of view by the total surface area;

[0139] The average pore diameter of the support layer is tested by: measuring the diameters of all visible pores in the field of view by scanning electron microscopy and calculating the average value;

[0140] The test method for the viscosity of silicone rubber at 25°C is as follows: using a rotor viscometer;

[0141] The test method of the cross-linking degree of the cross-linked polymer in the separation composite membrane C1 is: calculation by XPS and infrared spectroscopy;

[0142] The average pore size of the polymer layer is tested according to the standard GB / T 42269-2022 "Test method for pore size of separation membranes - gas permeation method";

[0143] The molar ratio of the linking group a to the linking group b can be calculated by the peak areas of the amide group and the ester group in the XPS spectrum;

[0144] The detection method of the thickness of each layer in the separation composite membrane is as follows: the thickness of the support layer is measured by using a spiral micrometer to measure the dry support layer, and the average value is calculated at 5 points, accurate to 1μm; the thickness of the silicone rubber middle layer is the average value of the transition part between the upper edge area of ​​the support layer and the lower edge area of ​​the top layer in the SEM image, accurate to 1nm; the thickness of the functional layer is the distance from the top surface of the entire membrane to the boundary of the support layer in the SEM image minus the thickness of the middle layer, accurate to 1nm;

[0145] The flux of CO2 and the flux of N2 are measured by the differential pressure method respectively. The specific method is in accordance with GB / T 1038.1-2022 "Test method for gas permeability of plastic film and sheeting - Part 1: Differential pressure method";

[0146] The calculation formula of the separation coefficient of CO2 and N2 is: separation coefficient of CO2 and N2 = flux of CO2 / flux of N2.

[0147] Polysulfone I (mass fraction of 20wt%), polysulfone II (mass fraction of 22wt%), polysulfone III (mass fraction of 18wt%), polysulfone IV (mass fraction of 16wt%), purchased by Solvay;

[0148] Polydimethylsiloxane, purchased from Adamas-Beta;

[0149] 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl spirobiindane, 9,9-bis(4-hydroxyphenyl)fluorene, diethylene glycol di(3-aminopropyl) ether, 1,4-bis(3-aminopropyl)piperazine, purchased by TCI;

[0150] Metaphenylenediamine, triethylenetetramine, tetraethylenepentamine, triethylamine, trimesoyl chloride, the purchasing company is Anaiji Chemical;

[0151] Sodium hydroxide and n-hexane were purchased from Sinopharm Reagents;

[0152] Isopar G, purchased by Aladdin Reagents.

[0153] Example 1

[0154] (1) Add 200 g of polysulfone I, 680 g of dimethylacetamide, 60 g of polyvinyl pyrrolidone, and 60 g of polyethylene glycol, heat to 70° C. for 24 h, prepare a support layer A1, and then wash with water for 48 h;

[0155] The weight average molecular weight of the material of the support layer A1 is 3500 Da, the porosity is 59%, and the average pore diameter is 21 nm.

[0156] (2) Using the casting method on the above 400cm 2 8 mL of 1 wt% polydimethylsiloxane solution was coated on the support layer A1, the scraper thickness was 100 μm, the coating curing temperature was 30° C., the coating curing time was 12 h, and the intermediate layer was cured to obtain a composite film B1;

[0157] The viscosity of the silicone rubber in the middle layer of the composite film B1 at 25° C. was 820 cP.

[0158] (3) Interfacial polymerization reaction at 25°C: add 0.4 g of trimesoyl chloride to 99.6 g of Isopar G solution, take 35 mL of the prepared oil phase solution, and mix the above 400 cm 2The composite membrane B1 was soaked in 35 mL of oil phase solution for 3 min. In the presence of 0.05 g of triethylamine, 0.1 g of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane was added to 99.75 g of water, 0.1 g of diethylene glycol di(3-aminopropyl) ether was added, and the pH was adjusted to 12 with sodium hydroxide. The composite membrane B1 soaked in the oil phase was soaked in 35 mL of aqueous solution for 5 min. After the interfacial polymerization reaction was completed, the residual solvent was fully washed with water to form a polymer layer containing a cross-linked polymer (structural unit I was derived from diethylene glycol di(3-aminopropyl) ether, structural unit II was derived from trimesoyl chloride, and structural unit III was derived from 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane) to obtain a separation composite membrane C1. Total reflection infrared absorption spectrum analysis showed that there were connecting groups a and b in the cross-linked polymer.

[0159] Among them, the cross-linking degree of the cross-linked polymer in the separation composite membrane C1 is 55.3%;

[0160] The average pore size of the polymer layer is 0.37 nm.

[0161] Example 2

[0162] (1) Add 220 g of polysulfone II, 660 g of dimethylacetamide, 60 g of polyvinyl pyrrolidone, and 60 g of polyethylene glycol, heat to 70° C. for 24 h, prepare a support layer A2, and then wash with water for 48 h;

[0163] The weight average molecular weight of the material of the support layer A2 is 3500 Da, the porosity is 56%, and the average pore diameter is 14 nm.

[0164] (2) Using the casting method on the above 400cm 2 8 mL of 0.5 wt% polydimethylsiloxane solution was coated on the support layer A2, the scraper thickness was 100 μm, the coating curing temperature was 30° C., the coating curing time was 12 h, and the intermediate layer was cured to obtain a composite membrane B2;

[0165] The viscosity of the silicone rubber in the middle layer of the composite film B2 at 25° C. is 450 cP.

[0166] (3) Interfacial polymerization reaction was carried out at 25°C: 0.6 g of trimesoyl chloride was added to 99.4 g of n-hexane solution, 35 mL of the prepared oil phase solution was taken, and the above 400 cm 2The composite membrane B2 was soaked in 35 mL of oil phase solution for 3 min. In the presence of 0.05 g of triethylamine, 0.04 g of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane and 0.16 g of 1,4-bis(3-aminopropyl)piperazine were added to 99.75 g of water. The pH was adjusted to 12 using sodium hydroxide. The composite membrane B2 soaked in the oil phase was soaked in 35 mL of aqueous solution for 1 min. After the interfacial polymerization reaction was completed, the residual solvent was fully washed with water to form a polymer layer containing a cross-linked polymer (structural unit I was derived from 1,4-bis(3-aminopropyl)piperazine, structural unit II was derived from trimesoyl chloride, and structural unit III was derived from 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane) to obtain a separation composite membrane C2. Total reflection infrared absorption spectroscopy analysis showed that linking groups a and b existed in the cross-linked polymer.

[0167] Wherein, the cross-linking degree of the cross-linked polymer in the separation composite membrane C2 is 60.5%;

[0168] Among them, the average pore size of the polymer layer is 0.34nm;

[0169] Figure 1 is the total reflection infrared absorption spectrum of the surface layer of the separation composite membrane C2 prepared in Example 2. -1 Peak, proof The presence of; at 1640cm -1 Peak, proof existence.

[0170] Example 3

[0171] (1) Add 180 g of polysulfone III, 700 g of dimethylacetamide, 60 g of polyvinyl pyrrolidone, and 60 g of polyethylene glycol, heat to 70° C. for 24 h, prepare a support layer A3, and then wash with water for 48 h;

[0172] The weight average molecular weight of the material of the support layer A3 is 3500 Da, the porosity is 66%, and the average pore diameter is 25 nm.

[0173] (2) Using the casting method on the above 400cm 2 8 mL of 1 wt% polydimethylsiloxane solution was coated on the support layer A3, the scraper thickness was 100 μm, the coating curing temperature was 30° C., the coating curing time was 12 h, and the intermediate layer was cured to obtain a composite membrane B3;

[0174] The viscosity of the silicone rubber in the middle layer of the composite film B3 at 25° C. is 820 cP.

[0175] (3) Interfacial polymerization reaction at 25°C: 0.4 g of trimesoyl chloride was added to 99.6 g of Isopar E solution to prepare an oil phase solution with a concentration of 0.4 wt%. 35 mL of the prepared oil phase solution was taken and mixed with the above 400 cm 2 The composite membrane B3 was immersed in 35 mL of oil phase solution for 3 min. In the presence of 0.05 g of triethylamine, 0.04 g of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane was added to 99.75 g of water, 0.16 g of triethylenetetramine was added, and the pH was adjusted to 12 with sodium hydroxide. The composite membrane B3 immersed in the oil phase was immersed in 35 mL of aqueous phase solution for 3 min. After the interfacial polymerization reaction was completed, the residual solvent was fully washed with water to form a polymer layer containing a cross-linked polymer (structural unit I was derived from triethylenetetramine, structural unit II was derived from trimesoyl chloride, and structural unit III was derived from 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane), and a separation composite membrane C3 was obtained.

[0176] Among them, the cross-linking degree of the cross-linked polymer in the separation composite membrane C3 is 63%;

[0177] The average pore size of the polymer layer is 0.33 nm.

[0178] Example 4

[0179] (1) Add 160 g of polysulfone IV, 720 g of dimethylacetamide, 60 g of polyvinyl pyrrolidone, and 60 g of polyethylene glycol, heat to 70° C. for 24 h, prepare a support layer A4, and then wash with water for 48 h;

[0180] The weight average molecular weight of the material of the support layer A4 is 3500 Da, the porosity is 71%, and the average pore diameter is 26 nm.

[0181] (2) Using the casting method on the above 400cm 2 8 mL of 1 wt% polydimethylsiloxane solution was coated on the support layer A4, the scraper thickness was 100 μm, the coating curing temperature was 30° C., the coating curing time was 12 h, and the intermediate layer was cured to obtain a composite film B4;

[0182] The viscosity of the silicone rubber in the middle layer of the composite film B4 at 25° C. is 820 cP.

[0183] (3) Interfacial polymerization reaction at 25°C: 0.4 g of trimesoyl chloride was added to 99.6 g of Isopar G solution to prepare an oil phase solution with a concentration of 0.4 wt%. 35 mL of the prepared oil phase solution was taken and mixed with the above 400 cm 2The composite membrane B4 was immersed in 35 mL of oil phase solution for 3 min. In the presence of 0.05 g of triethylamine, 0.04 g of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane was added to 99.75 g of water, 0.16 g of m-phenylenediamine was added, and the pH was adjusted to 11 with sodium carbonate. The composite membrane B4 immersed in the oil phase was immersed in 35 mL of aqueous solution for 3 min. After the interfacial polymerization reaction was completed, the residual solvent was fully washed with water to form a polymer layer containing a cross-linked polymer (structural unit I was derived from m-phenylenediamine, structural unit II was derived from trimesoyl chloride, and structural unit III was derived from 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane), and a separation composite membrane C4 was obtained.

[0184] Among them, the cross-linking degree of the cross-linked polymer in the separation composite membrane C4 is 61.8%;

[0185] The average pore size of the polymer layer is 0.34 nm.

[0186] Example 5

[0187] The method of Example 1 was followed, except that in step (3), "0.1 g of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane" was replaced with "0.1 g of 9,9-bis(4-hydroxyphenyl)fluorene" to obtain separation composite membrane C5;

[0188] Among them, the cross-linking degree of the cross-linked polymer in the separation composite membrane C5 is 57.2%;

[0189] The average pore size of the polymer layer is 0.36 nm.

[0190] Example 6

[0191] The method of Example 1 was followed, except that in step (3), "0.08 g of 9,9-bis(4-hydroxyphenyl)fluorene" was used to replace "0.1 g of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane", and "0.12 g of tetraethylenepentamine" was used to replace "0.1 g of diethylene glycol di(3-aminopropyl) ether", to obtain separation composite membrane C6;

[0192] Among them, the cross-linking degree of the cross-linked polymer in the separation composite membrane C6 is 60.9%;

[0193] The average pore size of the polymer layer is 0.33 nm.

[0194] Example 7

[0195] Step (1) is carried out according to the method of Example 2, except that the specific methods of steps (2) and (3) are as follows:

[0196] (2) Using the casting method on the above 400cm 2 8 mL of 2 wt% polydimethylsiloxane solution was coated on the support layer A7, the scraper thickness was 500 μm, the coating curing temperature was 50° C., the coating curing time was 48 h, and the intermediate layer was cured to obtain a composite membrane B7;

[0197] The viscosity of the silicone rubber in the middle layer of the composite film B7 at 25° C. was 1300 cP.

[0198] (3) Interfacial reaction at 25°C: add 0.6 g of trimesoyl chloride to 99.4 g of n-hexane solution, take 35 mL of the prepared oil phase solution, and mix the above 400 cm 2 The composite membrane B7 was immersed in 35 mL of oil phase solution for 3 min. In the presence of 0.05 g of triethylamine, 0.04 g of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane was added to 99.75 g of water, 0.16 g of m-phenylenediamine was added, and the pH was adjusted to 12 with sodium hydroxide. The composite membrane B7 immersed in the oil phase was immersed in 35 mL of aqueous phase solution for 15 min. After the interfacial polymerization reaction was completed, the residual solvent was fully washed with water to form a polymer layer containing a cross-linked polymer (structural unit I was derived from m-phenylenediamine, structural unit II was derived from trimesoyl chloride, and structural unit III was derived from 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane), and a separation composite membrane C7 was obtained.

[0199] Among them, the cross-linking degree of the cross-linked polymer in the separation composite membrane C7 is 64.1%;

[0200] Among them, the average pore size of the polymer layer is 0.2nm;

[0201] The film section of Example 7 was tested by electron microscope. Figure 2 As shown, it can be seen from the electron microscope image that the composite membrane C7 has a three-layer structure. The surface of the support layer is composed of a thicker intermediate layer and a thinner separation layer. The boundary between the intermediate layer and the separation layer is not obvious, which proves that the intermediate layer and the separation layer can fit tightly.

[0202] Example 8

[0203] Step (1) is carried out according to the method of Example 1, except that the specific methods of steps (2) and (3) are as follows:

[0204] (2) Using the casting method on the above 400cm 2 8 mL of 0.5 wt% polydimethylsiloxane solution was coated on the support layer A8, the scraper thickness was 100 μm, the coating curing temperature was 30° C., the coating curing time was 12 h, and the intermediate layer was cured to obtain a composite membrane B8;

[0205] The viscosity of the silicone rubber in the middle layer of the composite film B8 at 25° C. was 450 cP.

[0206] (3) Interfacial reaction at 25°C: add 0.6 g of trimesoyl chloride to 99.4 g of n-hexane solution, take 35 mL of the prepared oil phase solution, and mix the above 400 cm 2 The composite membrane B8 was immersed in 35 mL of oil phase solution for 3 min. In the presence of 0.05 g of triethylamine, 0.16 g of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane was added to 99.75 g of water, 0.04 g of m-phenylenediamine was added, and the pH was adjusted to 11 with sodium carbonate. The composite membrane B8 immersed in the oil phase was immersed in 35 mL of aqueous solution for 1 min. After the interfacial polymerization reaction was completed, the residual solvent was fully washed with water to form a polymer layer containing a cross-linked polymer (structural unit I was derived from m-phenylenediamine, structural unit II was derived from trimesoyl chloride, and structural unit III was derived from 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane), and a separation composite membrane C8 was obtained.

[0207] Among them, the cross-linking degree of the cross-linked polymer in the separation composite membrane C8 is 49.4%;

[0208] The average pore size of the polymer layer is 0.54 nm.

[0209] Example 9

[0210] The method of Example 1 was followed, except that in step (3), "1 g of trimesoyl chloride" was used instead of "0.4 g of trimesoyl chloride", to obtain separation composite membrane C9;

[0211] Among them, the cross-linking degree of the cross-linked polymer in the separation composite membrane C9 is 50.1%;

[0212] The average pore size of the polymer layer is 0.31 nm.

[0213] Example 10

[0214] The method of Example 1 was followed, except that in step (3), "2.5 g of trimesoyl chloride" was used instead of "0.4 g of trimesoyl chloride", to obtain separation composite membrane C10;

[0215] Among them, the cross-linking degree of the cross-linked polymer in the separation composite membrane C10 is 46.7%;

[0216] The average pore size of the polymer layer is 0.3 nm.

[0217] Embodiment 11

[0218] The method of Example 1 is different in that the specific method of step (3) is as follows:

[0219] Carry out interfacial polymerization at 25°C: add 0.4 g of trimesoyl chloride to 99.6 g of Isopar G solution, take 35 mL of the prepared oil phase solution, and mix the above 400 cm 2 The composite membrane B11 was immersed in 35 mL of the oil phase solution for 3 min. In the presence of 0.05 g of triethylamine, 0.4 g of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane was added to 99.15 g of water, 0.4 g of diethylene glycol di(3-aminopropyl) ether was added, and the pH was adjusted to 12 with sodium hydroxide. The composite membrane B10 immersed in the oil phase was immersed in 35 mL of the aqueous solution for 5 min. After the interfacial polymerization reaction was completed, the residual solvent was fully washed with water to form a polymer layer containing a cross-linked polymer (structural unit I was derived from diethylene glycol di(3-aminopropyl) ether, structural unit II was derived from trimesoyl chloride, and structural unit III was derived from 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane), and a separation composite membrane C11 was obtained.

[0220] Among them, the cross-linking degree of the cross-linked polymer in the separation composite membrane C11 is 64.7%;

[0221] The average pore size of the polymer layer is 0.26 nm.

[0222] Example 12

[0223] The method of Example 1 is different in that the specific method of step (3) is as follows:

[0224] (3) Interfacial polymerization reaction at 25°C: add 0.4 g of trimesoyl chloride to 99.6 g of Isopar G solution, take 35 mL of the prepared oil phase solution, and mix the above 400 cm 2 The composite membrane B12 was immersed in 35 mL of oil phase solution for 3 min. In the presence of 0.05 g of triethylamine, 1.2 g of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane was added to 97.55 g of water, 1.2 g of diethylene glycol di(3-aminopropyl) ether was added, and the pH was adjusted to 12 with sodium hydroxide. The composite membrane B12 immersed in the oil phase was immersed in 35 mL of aqueous solution for 5 min. After the interfacial polymerization reaction was completed, the residual solvent was fully washed with water to form a polymer layer containing a cross-linked polymer (structural unit I was derived from diethylene glycol di(3-aminopropyl) ether, structural unit II was derived from trimesoyl chloride, and structural unit III was derived from 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane), and a separation composite membrane C12 was obtained.

[0225] Among them, the cross-linking degree of the cross-linked polymer in the separation composite membrane C12 is 66.9%;

[0226] The average pore size of the polymer layer is 0.31 nm.

[0227] Example 13

[0228] The method of Example 1 is followed, except that in step (3), "carrying out interfacial polymerization reaction at 15°C" is used instead of "carrying out interfacial polymerization reaction at 25°C" to obtain separation composite membrane C13.

[0229] Among them, the cross-linking degree of the cross-linked polymer in the separation composite membrane C13 is 43.2%;

[0230] The average pore size of the polymer layer is 0.4 nm.

[0231] Comparative Example 1

[0232] The method of Example 1 is different in that the specific method of step (3) is as follows:

[0233] (3) Interfacial polymerization was carried out at 25°C. 0.4 g of trimesoyl chloride was added to 99.6 g of Isopar G solution. 35 mL of the prepared oil phase solution was taken and the above 400 cm 2 The composite membrane B1 was immersed in 35 mL of oil phase solution for 3 min. In the presence of 0.05 g of triethylamine, 0.2 g of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane was added to 99.75 g of water, and the pH was adjusted to 12 with sodium hydroxide. The composite membrane B1 after oil phase infiltration was immersed in 35 mL of aqueous solution for 5 min. After the interfacial polymerization reaction was completed, the residual solvent was thoroughly washed with water to obtain the separation composite membrane D1.

[0234] Comparative Example 2

[0235] The method of Example 1 is different in that the specific method of step (3) is as follows:

[0236] (4) An interfacial polymerization reaction was carried out at 25°C. 0.4 g of trimesoyl chloride was added to 99.6 g of n-hexane solution. 35 mL of the prepared oil phase solution was taken and the above 400 cm 2 The composite membrane B1 was immersed in 35 mL of oil phase solution for 3 min. In the presence of 0.05 g of triethylamine, 0.2 g of m-phenylenediamine was added to 99.75 g of water, and the pH was adjusted to 12 with sodium hydroxide. The composite membrane B1 after oil phase infiltration was immersed in 35 mL of aqueous solution for 1 min. After the interfacial polymerization reaction was completed, the residual solvent was thoroughly washed with water to obtain the separation composite membrane D2.

[0237] The molar ratios of the linking group a to the linking group b contained in the separation composite membranes C1-C13, D1 and D2 are shown in Table 1.

[0238] Table 1

[0239] Molar ratio of linking group a to linking group b C1 1.04:1 C2 4.27:1 C3 4.58:1 C4 4.06:1 C5 1.20:1 C6 1.59:1 C7 4.82:1 C8 0.89:1 C9 1.07:1 C10 1.13:1 C11 1.01:1 C12 1.04:1 C13 1.25:1 D1 0:1 D2 -

[0240] The performance parameters of separation composite membranes C1-C13, D1 and D2 are shown in Table 2.

[0241] Table 2

[0242]

[0243]

[0244] At 25°C and 0.15 MPa, the CO2 flux and the separation coefficient of CO2 and N2 of the separation composite membranes C1-C13, D1 and D2 were tested respectively. The results are shown in Table 3.

[0245] Table 3

[0246] serial number <![CDATA[Flux of CO2 (GPU)]]> <![CDATA[Separation coefficient of CO2 and N2]]> C1 725 65 C2 604 67 C3 387 53 C4 610 74 C5 552 50 C6 364 51 C7 221 78 C8 832 34 C9 260 49 C10 192 45 C11 213 63 C12 207 40 C13 502 31 D1 1280 24 D2 150 71

[0247] pass Figure 1 It can be seen from the peak position of the infrared spectrum that there is a polymer layer in the separation composite membrane. From the results of Table 1 and Table 2, it can be seen that the separation composite membrane prepared by the present invention has excellent CO2 flux and a higher separation coefficient of CO2 and N2.

[0248] By comparing Example 1 with Example 9 and Example 10, it can be seen that the amount of oil phase monomer used will affect the final CO2 flux and the higher separation coefficient of CO2 and N2; when the amount of oil phase monomer used is too high, the thickness of the polymer layer will increase, the CO2 flux will decrease, and the separation coefficient of CO2 and N2 will be reduced;

[0249] By comparing Example 1 with Example 11 and Example 12, it can be seen that the amount of water-phase monomer used will affect the final CO2 flux and the higher separation coefficient of CO2 and N2. When the amount of water-phase monomer used is too high, the thickness of the polymer layer will increase, the CO2 flux will decrease, and the separation coefficient of CO2 and N2 will be reduced.

[0250] By comparing Example 1 with Comparative Example 1, it can be seen that when there are only polyphenol compounds in the aqueous phase solution, due to the non-planar structure of the polyphenol compounds, the internal cavity of the polymer in the prepared separation composite membrane is large, so the CO2 flux of Comparative Example 1 is much higher than that of Example 1, but the separation coefficient of CO2 and N2 in Comparative Example 1 is greatly reduced, and the gas selectivity separation performance of the separation composite membrane is poor.

[0251] By comparing Example 1 with Comparative Example 2, it can be seen that when there is only a polyamine compound in the aqueous phase solution, due to the presence of amino groups in the polyamine compound that do not participate in the reaction, the amino groups have a good affinity for CO2 and can promote CO2, and the separation composite membrane has good gas selectivity. However, the polymer prepared by the reaction of polyacyl chlorides and polyamine compounds is thick, which makes the overall thickness of the separation composite membrane high, and the flux of CO2 of the separation composite membrane is greatly reduced.

[0252] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A separation composite membrane, characterized in that: The separation composite membrane comprises a support layer, a silicone rubber intermediate layer and a polymer layer stacked in sequence; The cross-linked polymer constituting the polymer layer includes a structural unit I derived from a polyamine compound, a structural unit II derived from a polyacyl chloride compound, and a structural unit III derived from a polyphenol compound.

2. The separation composite membrane according to claim 1, wherein The cross-linked polymer also comprises the general formula The connecting group a connecting the structural unit I and the structural unit II shown in the general formula The connecting group b connecting the structural unit II and the structural unit III shown; Preferably, the molar ratio of the linking group a to the linking group b is 0.1-10:1, preferably 0.5-5:

1.

3. The separation composite membrane according to claim 1 or 2, wherein: The polyamine compound is selected from at least one of m-phenylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, 1,4-cyclohexanediamine, 1,3-diamino-2-methylpropane, bis(2-aminoethyl) ether, ethylene glycol bis(2-aminoethyl) ether, diethylene glycol di(3-aminopropyl) ether, 1,4-butanediol bis(3-aminopropyl) ether and 1,4-bis(3-aminopropyl) piperazine, preferably at least one of triethylenetetramine, tetraethylenepentamine, diethylene glycol di(3-aminopropyl) ether and 1,4-bis(3-aminopropyl) piperazine; and / or, the polybasic acid chloride compound is at least one selected from trimesoyl chloride, isophthaloyl chloride and 3,3,4,4-biphenyltetracarboxylic acid chloride, preferably trimesoyl chloride; And / or, the polyphenol compound is selected from at least one of phloroglucinol, 1,2,4,5-pyrogallol, 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane, 9,9-bis(4-hydroxyphenyl)fluorene and 2,2',3,3'-tetrahydroxy-1,1'-binaphthyl, preferably selected from 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane and / or 9,9-bis(4-hydroxyphenyl)fluorene.

4. The separation composite membrane according to any one of claims 1 to 3, wherein: The silicone rubber intermediate layer comprises silicone rubber; Preferably, the viscosity of the silicone rubber at 25° C. is 0.1-50000 cP, preferably 50-4000 cP.

5. The separation composite membrane according to any one of claims 1 to 4, wherein: The material constituting the support layer is polysulfone and / or polyethersulfone; Preferably, the weight average molecular weight of the material of the support layer is 2000-400000Da, preferably 3000-6000Da; Preferably, the support layer has a porous structure; Preferably, the porosity of the support layer is 10-80%, preferably 40-70%; Preferably, the average pore size of the support layer is 1-5000 nm, preferably 5-200 nm.

6. The separation composite membrane according to any one of claims 1 to 5, wherein: The average thickness of the support layer is 20-500 μm, the average thickness of the silicone rubber intermediate layer is 50-900 nm, and the average thickness of the polymer layer is 10-500 nm; Preferably, the average thickness of the support layer is 60-150 μm, the average thickness of the silicone rubber intermediate layer is 50-500 nm, and the average thickness of the polymer layer is 50-250 nm; Preferably, the cross-linking degree of the cross-linked polymer is 40-70%, preferably 50-65%; Preferably, the polymer layer has a microporous structure; Preferably, the average pore size of the polymer layer is 0.1-1 nm, preferably 0.3-0.6 nm.

7. The separation composite membrane according to any one of claims 1 to 6, wherein: The CO2 flux of the separation composite membrane is ≥200GPU, preferably ≥350GPU; Preferably, the separation coefficient of CO2 and N2 of the separation composite membrane is ≥30, preferably ≥50.

8. A method for preparing a separation composite membrane, characterized in that: The method comprises: (1) preparing a casting solution and heating it, preparing a support layer by a non-solvent phase conversion method, and then washing it with water; (2) applying the silicone rubber solution on the support layer by scraping, and performing coating and curing treatment to form a silicone rubber intermediate layer on the support layer; (3) preparing a polymer layer on the silicone rubber intermediate layer by interfacial polymerization of oil phase monomers in the oil phase solution and water phase monomers in the water phase solution to obtain the separation composite membrane; Wherein, the oil phase monomer is selected from polyacyl chloride compounds; The aqueous phase monomer is selected from polyamine compounds and polyphenol compounds.

9. The method according to claim 8, wherein: In step (1), the casting solution comprises dimethylacetamide, polysulfone and a casting additive; Preferably, the casting additive is selected from polyvinyl pyrrolidone and / or polyethylene glycol; Preferably, based on the total weight of the casting solution, the content of dimethylacetamide is 60wt%-80wt%, the content of polysulfone is 16wt%-24wt%, and the content of the casting additive is 10wt%-15wt%; Preferably, based on the total weight of the casting solution, the content of dimethylacetamide is 65wt%-75wt%, the content of polysulfone is 18wt%-22wt%, and the content of the casting additive is 12wt%-14wt%; Preferably, the heating temperature is 50-90°C, preferably 65-80°C, and the heating time is 12-72h, preferably 24-70h; Preferably, the water washing time is ≥12 h; preferably ≥36 h.

10. The method according to claim 8 or 9, wherein: In step (2), the silicone rubber solution is a polysiloxane solution, preferably a polydimethylsiloxane solution; Preferably, the concentration of the silicone rubber solution is 0.5wt%-5wt%, preferably 1wt%-2.5wt%; Preferably, the scraping method is to use a scraper for scraping, and the scraper thickness is 50-500 μm, preferably 100-150 μm; Preferably, the coating curing temperature is 25-70°C, preferably 30-55°C; the coating curing time is 0.5-48h, preferably 8-16h.

11. The method according to any one of claims 8 to 10, wherein: In step (3), the weight ratio of the aqueous phase monomer to the oil phase monomer is 1:1-5, preferably 1:2-4; Preferably, in the aqueous phase solution, the concentration of the aqueous phase monomer is 0.05wt%-2wt%, preferably 0.1wt%-0.3wt%; Preferably, in the oil phase solution, the concentration of the oil phase monomer is 0.05wt%-2wt%, preferably 0.2wt%-0.6wt%; Preferably, in the aqueous phase solution, the concentration of the polyphenol compound is 0.02wt%-0.15wt%, preferably 0.04wt%-0.1wt%; Preferably, in the aqueous phase solution, the concentration of the polyamine compound is 0.05wt%-0.2wt%, preferably 0.1wt%-0.18wt%; Preferably, the weight ratio of the polyamine compound: the polyphenol compound is 0.1-9:1, preferably 0.2-4:1; Preferably, the polyphenol compound is selected from at least one of phloroglucinol, 1,2,4,5-pyrogallol, 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane, 9,9-bis(4-hydroxyphenyl)fluorene and 2,2',3,3'-tetrahydroxy-1,1'-binaphthyl, preferably selected from 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethylspirobisindane and / or 9,9-bis(4-hydroxyphenyl)fluorene; Preferably, the polyamine compound is selected from at least one of m-phenylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, 1,4-cyclohexanediamine, 1,3-diamino-2-methylpropane, bis(2-aminoethyl)ether, ethylene glycol bis(2-aminoethyl)ether, diethylene glycol di(3-aminopropyl)ether, 1,4-butanediol bis(3-aminopropyl)ether and 1,4-bis(3-aminopropyl)piperazine, preferably selected from at least one of triethylenetetramine, tetraethylenepentamine, diethylene glycol di(3-aminopropyl)ether and 1,4-bis(3-aminopropyl)piperazine; Preferably, the polybasic acyl chloride compound is selected from at least one of trimesoyl chloride, isophthaloyl chloride and 3,3,4,4-biphenyltetrachloride, preferably trimesoyl chloride; Preferably, the oil phase solution further comprises an oil phase solvent, and the oil phase solvent is selected from at least one of n-hexane, n-heptane and isoparaffin; Preferably, the isoparaffin is selected from Iospar G and / or Isopar E.

12. The method according to any one of claims 8 to 11, wherein: The interfacial polymerization reaction further comprises adding an additive to the aqueous solution to adjust the pH of the interfacial polymerization reaction to 9-13, preferably 10-12; Preferably, the additive is selected from sodium hydroxide and / or sodium carbonate; Preferably, the process of the interfacial polymerization reaction further comprises: bringing the upper surface of the silicone rubber intermediate layer into first contact with the oil phase solution, and then bringing the upper surface into second contact with the water phase solution; Preferably, the first contacting time is 2-10 min, preferably 3-5 min; Preferably, the reaction temperature of the interfacial polymerization reaction is 15-50° C., preferably 20-30° C.; the reaction time of the interfacial polymerization reaction is 0.5-60 min, preferably 1-5 min.

13. A separation composite membrane obtained by the preparation method according to any one of claims 8 to 12.

14. Use of the separation composite membrane according to any one of claims 1 to 7 and 13 in CO2 separation.

Citation Information

Patent Citations

  • Polyether-b-polyamide multilayer composite film and preparation method thereof

    CN102451621A

  • Self-microporous high-flux nano-filtration composite membrane and preparation method thereof

    CN109289543A

  • Membrane casting solution, ultrafiltration base membrane, preparation method of ultrafiltration base membrane, and separation membrane

    CN110756064A

  • Method for preparing high-performance carbon dioxide separation composite membrane containing twisted structure through interfacial polymerization

    CN113522040A

  • Separation membrane as well as preparation method and application thereof

    CN114432910A

Cited By

  • Method for recovering carbon dioxide in oil field gas through membrane separation

    CN120019860A